Point of departure : returning to our more authentic worldview for education and survival - Jacobs, Donald Trent, 1946- (Emerald Publishing Limited : Information Age Publishing, Inc., 2016)
Point of Departure offers a practical metacognitive and transformational learning strategy for human surviving and thriving. Using five foundational and interactive Indigenous worldview beliefs that contrast sharply with our dominant worldview ones, everyone can reclaim the original instructions for living on Earth. Without the resulting change in consciousness that can emerge from this learning approach, no modern technologies can save us. The five foundational Indigenous precepts relate to a radically different understanding about: (1) Trance-based learning (2) Courage and Fearlessness (3) Community Oriented Self-Authorship (4) Sacred Communications (5) Nature as Ultimate Teacher.